Culture-based and molecular investigation of antibiotic and metal resistance in a semi-arid agricultural soil repeatedly amended with urban sewage sludge - Sonia Mokni-Tlili (20487266) (2024)
Unsustainable agricultural intensification and climate change effects have caused chronic soil depletion in most arid and semi-arid croplands. As such, the land application of urban sewage sludge (USS) has been regulated in several countries as an alternative soil conditioner with recycling benefits. However, the risks of multi-contamination have made its agricultural reuse debatable. Accordingly, this study explored the long-term the impact of repetitive USS applications with increasing rates (0, 40, 80, and 120 tha−1 year−1) on a sandy soil properties. A special focus was on the spread of antibiotic-resistant bacteria, metal-resistant bacteria and corresponding resistance genes in soil (ARB, MRB, ARGs and MRGs, respectively). The outcomes showed a dose-dependent variation of different soil parameters including the increase of heavy metal content and total heterotrophic bacteria (THB) up to the highest sludge application rate. Besides, the two last sludge lots applied in fall 2019 and 2020 contained cultivable ARB for all addressed antibiotics at much higher counts than in corresponding treated soils. Interestingly, the average index of antibiotic resistance (ARB/THB) increased in the USS used in fall 2020 compared to 2019 (from 6.2% to 9.4%). This indicates that factors such as fluctuations in wastewater quality, treatments operations, and extensive antibiotic use following the outbreak of the COVID-19 pandemic in early 2020 could have caused this variation. The molecular assessment of bacterial resistance resulted in the identification of three ARGs (mefA, sul1 and sul2), one MRG (czcA) and one integron (intI1). This might have implications on resistance co-selection, which can pose a threat to human health via contaminated crops. Other Information Published in: Environmental Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.envres.2024.120182